Binaural Pitch Fusion in Children With Normal Hearing, Hearing Aids, and Cochlear Implants. Issue 6 (November 2020) - Hartling, Curtis L.; Fowler, Jennifer R.; Stark, Gemaine N.; Glickman, Bess; Eddolls, Morgan; Oh, Yonghee; Ramsey, Katrina; Reiss, Lina A. J.
Abstract : Objectives: Binaural pitch fusion is the perceptual integration of stimuli that evoke different pitches between the ears into a single auditory image. Adults who use hearing aids (HAs) or cochlear implants (CIs) often experience abnormally broad binaural pitch fusion, such that sounds differing in pitch by as much as 3 to 4 octaves are fused across ears, leading to spectral averaging and speech perception interference. The main goal of this study was to measure binaural pitch fusion in children with different hearing device combinations and compare results across groups and with adults. A second goal was to examine the relationship of binaural pitch fusion to interaural pitch differences or pitch match range, a measure of sequential pitch discriminability. Design: Binaural pitch fusion was measured in children between the ages of 6.1 and 11.1 years with bilateral HAs (n = 9), bimodal CI (n = 10), bilateral CIs (n = 17), as well as normal-hearing (NH) children (n = 21). Depending on device combination, stimuli were pure tones or electric pulse trains delivered to individual electrodes. Fusion ranges were measured using simultaneous, dichotic presentation of reference and comparison stimuli in opposite ears, and varying the comparison stimulus to find the range that fused with the reference stimulus. Interaural pitch match functions were measured using sequential presentation of reference and comparison stimuli, and varying the comparison stimulus to find the pitch match center and range. Results: Children with bilateral HAs had significantly broader binaural pitch fusion than children with NH, bimodal CI, or bilateral CIs. Children with NH and bilateral HAs, but not children with bimodal or bilateral CIs, had significantly broader fusion than adults with the same hearing status and device configuration. In children with bilateral CIs, fusion range was correlated with several variables that were also correlated with each other: pure-tone average in the second implanted ear before CI, and duration of prior bilateral HA, bimodal CI, or bilateral CI experience. No relationship was observed between fusion range and pitch match differences or range. Conclusions: The findings suggest that binaural pitch fusion is still developing in this age range and depends on hearing device combination but not on interaural pitch differences or discriminability. Abstract : Supplemental Digital Content is available in the text.